2017
DOI: 10.5194/acp-17-13265-2017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term chemical analysis and organic aerosol source apportionment at nine sites in central Europe: source identification and uncertainty assessment

Abstract: Abstract. Long-term monitoring of organic aerosol is important for epidemiological studies, validation of atmospheric models, and air quality management. In this study, we apply a recently developed filter-based offline methodology using an aerosol mass spectrometer (AMS) to investigate the regional and seasonal differences of contributing organic aerosol sources. We present offline AMS measurements for particulate matter smaller than 10 µm at nine stations in central Europe with different exposure characteris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
127
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 98 publications
(149 citation statements)
references
References 56 publications
21
127
0
1
Order By: Relevance
“…Therefore, to reduce the possibility of spurious "anti-correlation" due to highly variable concentration ranges, data were amplitudenormalized prior to correlation analysis. A thorough discussion of the normalized cross-correlation method can be found elsewhere (Bardal and Saetran, 2016;Dai and Zhou, 2017;Eisner et al, 2009;Kaso, 2018;Lainer et al, 2016;Le Pichon et al, 2019). To achieve pair-wise correlation analysis between the sampling sites collected during the same periods, the original raw daily measurements were processed as follows: starting on identical days for each pairs of sites, the arrangement of the original daily data into consecutive 3 d intervals (or 6 d intervals in the case of OPE-ANDRA) and the calculation of the average concentration values for the middle day were performed.…”
Section: Data Analysesmentioning
confidence: 99%
“…Therefore, to reduce the possibility of spurious "anti-correlation" due to highly variable concentration ranges, data were amplitudenormalized prior to correlation analysis. A thorough discussion of the normalized cross-correlation method can be found elsewhere (Bardal and Saetran, 2016;Dai and Zhou, 2017;Eisner et al, 2009;Kaso, 2018;Lainer et al, 2016;Le Pichon et al, 2019). To achieve pair-wise correlation analysis between the sampling sites collected during the same periods, the original raw daily measurements were processed as follows: starting on identical days for each pairs of sites, the arrangement of the original daily data into consecutive 3 d intervals (or 6 d intervals in the case of OPE-ANDRA) and the calculation of the average concentration values for the middle day were performed.…”
Section: Data Analysesmentioning
confidence: 99%
“…The AMS measures the particle size-resolved bulk chemical composition, e.g. organic compounds, ammonium, nitrate, sulfate, and chloride, in mass concentrations with high time resolution and sensitivity (DeCarlo et al, 2006). Similarly as the LAAPTOF, aerosols are sampled with a flow rate of ∼ 84 cm 3 min −1 via a similar ADL (Peck et al, 2016) in the size range 70 nm to 2.5 µm d va and then pass through a PTOF chamber.…”
Section: Measurement Site and Instrumentationmentioning
confidence: 99%
“…Several studies of indoor air quality have identified cooking and in particular cooking using biomass or wood as a heating source as one of the most significant activities that generates indoor particles [33][34][35][36][37]. In fact, cooking and biomass burning emissions are among the main sources of particulate matter (PM) [38][39][40]. Different styles of cooking generate aerosols with typical mass concentrations, size distribution and chemical compositions, and the presence of well-known chemical carcinogens, such as PAHs (polycyclic aromatic hydrocarbons).…”
Section: Introductionmentioning
confidence: 99%